The Influence Of Originality, Quality, And Quantity On, Intention To Follow The Advice, Through Hedonic Experience, Opinion Leadership, And Perceived Aesthetics - Haryany Trifena Girsang; Dimas Angga Negoro (International Journal Labs, 2024)
Factors that determine the success of influencer marketing focusing on TikTok social network users This study examines the influence of influencer account characteristics (Perceived Originality Perceived Quantity, Perceived Quality), through Hedonic Experience, Opinion Leadership and Perceived Aesthetics and how this impacts their intention to Intention to Follow The Advice, if users feel that the content presented by an influencer is originality and has a large variety of content, they will tend to view the influencer as opinion leadership and, as a result are likely to follow the advice and recommendations of the influencer. The purpose of this study is to identify the determinants of influencer marketing success on TikTok and identify the characteristics that are most effective in attracting users on TikTok. This study was designed using purposive sampling method involving TikToker users and followers across Indonesia. quantitative research using partial least squares path modeling method (PLS-SEM). Some of the findings in this study are that there is no significant relationship between perceived aesthetics and intention to follow the advice and perceived originality has an indirect effect on opinion leadership. The managerial implication of this research for industry practitioners and researchers is that companies can design more targeted and effective marketing campaigns by understanding how perceived originality, quantity, and quality factors affect intention to follow the advice through hedonic experience. A thorough analysis with user preferences and an opportunity to build stronger and sustainable partnerships with the company's influencers and expand the reach of their campaigns, increasing the company's brand awareness.